Goldilocks and the three bears - Langley, Jonathan 1952- (HarperCollins Publishers, 1993)
While three bears are away from home, Goldilocks ventures inside their house, tastes their porridge, tries their chairs, and finally falls asleep in Baby Bear's bed
Keywords: Englisch; Märchen; Bär; Familie; Kind; Folklore / Juvenile literature; Bears / Folklore / Juvenile literature; Folklore; Bears / Folklore; Bears; Fiction; Juvenile works; Bilderbuch